USE OF A CHATBOT IN AUTOMATED INFORMATION SYSTEM FOR PROCESS MANAGEMENT IN EDUCATION: USE OF A CHATBOT IN AUTOMATED INFORMATION SYSTEM FOR PROCESS MANAGEMENT IN EDUCATION - Ivanova, Desislava; Atanasov, Valentin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
This scientific paper presents a role-based aspect of chatbots in the educational field, covering certain of their advantages and disadvantages. Future trends in their development are presented. The use and implementation of chatbots in an automated information system for process management in the educational field is discussed.